Historical-qualitative analysis of breastfeeding trends in three OECD countries - Amanda Marie Lubold (BMC, 2019)
Abstract Background Breastfeeding rates among high income, western countries vary considerably. This research examines three countries, Sweden, Ireland, and the United States, with respect to both public health initiatives and policy initiatives. Methods This article uses a historical qualitative analysis of breastfeeding rates over time. It uses the welfare state structure as a framework for understanding the variation in breastfeeding outcomes among these three countries. Results With its strong family policies and early adherence to international public health recommendations, Sweden was able to build high rates of breastfeeding initiation and duration. However, Sweden's breastfeeding rates have been declining, which may be a result of increasing encouragement for fathers to take equal leave, and because Sweden is no longer prioritizing breastfeeding in its public health goals. Ireland has experienced rapid growth of both breastfeeding initiation and participation in the Baby-Friendly Hospital Initiative, though its rates still lag behind much of the Western world. The United States has seen increases in participation with the Baby-Friendly Hospital Initiative, but lacks state support in public health and labor policies. Conclusion This analysis suggests that in a country with a strong welfare state and early adoption of internationally recommended public policy, breastfeeding is able to flourish. It also suggests that the Baby-Friendly hospital Initiative is a predictor of breastfeeding success.